Altered metabolite accumulation in tomato fruits by coexpressing a feedback‐insensitive AroG and the PhODO1 MYB‐type transcription factor. Issue 12 (22nd June 2016) - Xie, Qingjun; Liu, Zhongyuan; Meir, Sagit; Rogachev, Ilana; Aharoni, Asaph; Klee, Harry J.; Galili, Gad
Summary: Targeted manipulation of phenylalanine (Phe) synthesis is a potentially powerful strategy to boost biologically and economically important metabolites, including phenylpropanoids, aromatic volatiles and other specialized plant metabolites. Here, we use two transgenes to significantly increase the levels of aromatic amino acids, tomato flavour‐associated volatiles and antioxidant phenylpropanoids. Overexpression of the petunia MYB transcript factor, ODORANT1 ( ODO1 ), combined with expression of a feedback‐insensitive E. coli 3‐deoxy‐D‐arabino‐heptulosonate 7‐phosphate synthase ( AroG ), altered the levels of multiple primary and secondary metabolites in tomato fruit, boosting levels of multiple secondary metabolites. Our results indicate that coexpression of AroG and ODO1 has a dual effect on Phe and related biosynthetic pathways: (i) positively impacting tyrosine (Tyr) and antioxidant related metabolites, including ones derived from coumaric acid and ferulic acid; (ii) negatively impacting other downstream secondary metabolites of the Phe pathway, including kaempferol‐, naringenin‐ and quercetin‐derived metabolites, as well as aromatic volatiles. The metabolite profiles were distinct from those obtained with either single transgene. In addition to providing fruits that are increased in flavour and nutritional chemicals, coexpression of the two genes provides insights into regulation of branches of phenylpropanoid metabolic pathways.